2020
DOI: 10.1002/csc2.20384
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of extra‐early‐maturing yellow and orange quality protein maize inbreds and derived hybrids under low soil nitrogen and Striga infestation

Abstract: Ideas 1. General combining ability (GCA) effects were superior over specific combining ability (SCA) effects indicating that additive genes largely controlled grain yield and other traits among the newly developed extra-early quality protein maize inbred lines under low nitrogen, Striga-infested and high nitrogen conditions. 2. Maternal genetic effects influenced plant height under Striga-infested condition which suggested that inbred lines that exhibited significant and positive GCA-female effects for plant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
5
11
1
Order By: Relevance
“…Partitioning the QPM hybrids into genetic components, significant GCAm and GCAf mean squares were observed for grain yield and other measured traits under low-nitrogen environments implied that additive gene action was more important in the inheritance of grain yield and other measured traits under low-nitrogen. Similar findings were reported by Ifie et al [30], Annor and Badu-Apraku [31], Obeng-Bio et al [11], and Abu et al [32] on the preponderance of the additive gene action over the non-additive gene action in the inheritance of grain yield under low-nitrogen environments. Contrarily, studies by Makumbi et al [33], and Neolle et al [34] reported non-additive gene action to be more important in the inheritance of grain yield under low-nitrogen environments.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Partitioning the QPM hybrids into genetic components, significant GCAm and GCAf mean squares were observed for grain yield and other measured traits under low-nitrogen environments implied that additive gene action was more important in the inheritance of grain yield and other measured traits under low-nitrogen. Similar findings were reported by Ifie et al [30], Annor and Badu-Apraku [31], Obeng-Bio et al [11], and Abu et al [32] on the preponderance of the additive gene action over the non-additive gene action in the inheritance of grain yield under low-nitrogen environments. Contrarily, studies by Makumbi et al [33], and Neolle et al [34] reported non-additive gene action to be more important in the inheritance of grain yield under low-nitrogen environments.…”
Section: Discussionsupporting
confidence: 86%
“…The inconsistencies in the reports on the relative importance of the additive and non-additive gene action in the inheritance of grain yield and other traits call for the need for further studies to confirm the type of gene action controlling grain yield and other agronomic traits in the newly developed early maize QPM inbred lines in the IITA-MIP. Additionally, several studies have reported the preponderance of additive gene action over non-additive gene action in the inheritance of grain yield under low-nitrogen conditions [12,[30][31][32]. Contrarily, studies by Makumbi et al [33] and Badu-Apraku et al [26] reported that non-additive gene action conditioned the grain yield of maize hybrids under low-nitrogen, while Noelle et al [34] reported that both additive and non-additive genetic action conditioned grain yield when soil nitrogen was low.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the absence of clustering based on LN tolerance or tryptophan content is supported by previous finding of [ 65 , 66 ] who reported that clustering among a set of CIMMYT inbreds and open pollinated varieties was independent of the phenotype or environmental adaptations. The high genetic distances between inbreds from different source populations which caused them to be grouped under different clusters suggested that hybrid crosses between yellow and orange lines from different clusters would produce higher heterosis compared to crosses between only yellow or orange lines within to the same cluster [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seed samples of 65 (55 yellow plus 10 orange lines) selected inbred lines were dispatched to the Maize Nutritional Quality and Plant Tissue Analysis Laboratory of CIMMYT, for tryptophan analysis using the calorimetric method [ 24 ]. The 65 inbred lines were selected because they were newly developed lines with high levels of pro-vitamin A and/or lysine and tryptophan contents, and were also of major interest for the combining ability studies [ 6 ]. Tryptophan content of each genotype was estimated from two independent samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation